Application Of Criminal Sanctions Against Gambling Business Crime In The Kudus State Court Criminal Law And Policy In The Bill Book Of Laws Based On The Value Of Criminal Justice - Jajang Wiwoko; Eko Soponyono (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
The interest and research in this paper are to determine the application of the Criminal Sanctions Against Perpetrators of the Crime of Gambling in the Kudus District Court in the Criminal Law and Policy In the draft the Code of Penal The Value-Based Criminal Justice.This research is empirical legal research, the research is based on Application of Criminal Sanctions Against Perpetrators of the Crime of Gambling in the Kudus District Court in the Criminal Law and Policy In the draft the Code of Criminal Justice Based Values were analyzed quantitatively.The application of criminal sanctions against perpetrators of criminal acts gambling in the District Court of the KudusIn its decision 89 / Pid.Sus / 2016 / PN.Kds. Judges used a single indictment, namely Article 310 paragraph (4) of Act No. 22 of 2009 on Traffic and Transportation where elements of the indictment has been taken as proved by the judges. Where, between the act and the elements of each to the correct article. And by saving writer application of the substantive law in the case has been in accordance with the criminal law in Indonesia.Decision No. 89 / Pid.Sus / 2016 / PN.Kds. decisions proccess made by the judges opinion, Writers are in accordance with the applicable law as described by the author before, based on at least two a lack of legal evidence, where in the cases studied author, who used the judge evidence is witness testimony, evidence, letter post mortem and the testimony of the defendant.Keywords: Analysis of Law; Criminal Witness; Traffic Accidents.